Decentralizing governance emerging concepts and practices - Cheema, G. Shabbir (Washington, D.C. Brookings Institution Press, 2007)
"Assesses the emerging concepts of decentralization (devolution, empowerment, capacity building, and democratic governance) in different contexts and regions. Details the factors driving the movement, including political changes such as the fall of the Iron Curtain and the ascendance of democracy; economic factors such as globalization and outsourcing; and technological advances"
Includes bibliographical references and index.
Keywords: Decentralization in government